A Śaiva Utopia The Śivadharma's Revision of Brahmanical Varṇāśramadharma - Bisschop, Peter (Studies on the History of Śaivism, 2021)
A Śaiva Utopia centers on the eleventh chapter of the Śivadharmaśāstra, known as the Chapter on Śiva's Discipline (Śivāśramādhyāya). A critical edition and annotated English translation of the Sanskrit text of this chapter is preceded by a comprehensive study of the Śivadharma's revision of the Brahmanical 'laws on class and discipline' (varṇāśramadharma), tracing its utopian vision of a society bound by Śiva devotion. An edition and English translation of a Sanskrit commentary on the chapter, preserved on a unique palm leaf manuscript in Malayalam script, is included as well. The book concludes with an appendix, which addresses the revision of the Śivāśramādhyāya in the Bhaviṣyapurāṇa, where the Śivadharma has been turned into a Sauradharma ('religion of the Sun'). A Śaiva Utopia should be of interest to all historians of Indian religions.